Early neurodevelopmental characterization in children with cobalamin C/defect. Issue 2 (16th January 2020) - Ricci, Daniela; Martinelli, Diego; Ferrantini, Gloria; Lucibello, Simona; Gambardella, MLuigia; Olivieri, Giorgia; Chieffo, Daniela; Battaglia, Domenica; Diodato, Daria; Iarossi, Giancarlo; Donati, Alice M.; Dionisi‐Vici, Carlo; et al.
Abstract: Cobalamin C (cblC) defect is the most common inherited disorder of cobalamin metabolism. Developmental delay, behavioral problems, and maculopathy are common, but they have not been systematically investigated. The aim of this study was to define early neurodevelopment in cblC patients and the possible contribution of different factors, such as mode of diagnosis, age at diagnosis, presence of brain lesions and epilepsy. Children up to the age of 4 years with a visual acuity ≥1/10 were evaluated using the Griffiths' Mental Development Scales. Eighteen children were enrolled (age range 12‐48 months). Four were diagnosed by newborn screening (NBS); in the others mean age at diagnosis was 3.5 months (range 0.3‐18 months). Eight had seizures: three in the first year, and five after the second year of life. Fourteen had brain lesions on magnetic resonance imaging (MRI). Neurovisual assessment evidenced low visual acuity (<3/10) in 4/18. NBS diagnosed patients had higher general and subquotients neurodevelopmental scores, normal brain MRI, and no epilepsy. The others showed a progressive reduction of the developmental quotient with age and language impairment, which was evident after 24 months of age. Our findings showed a progressive neurodevelopmental deterioration and a specific fall in language development after 24 months in cblC defect. The presence of brain lesions and epilepsy was associated with a worst neurodevelopmental outcome. NBS, avoiding major disease‐related events and allowing an earlier treatment initiation, appeared to have a protective effect on the development of brain lesions and to promote a more favorable neurodevelopment.